Vpogled v socialno geografijo - Drozg, Vladimir (University of Maribor Press, 2020)
Insight in to Scoail Geography. Social geography analyses how people of different social characteristics function in space and how is their functioning in space reflected by the material things they use. In a socially increasingly diverse society, the space is also becoming more diverse and articulated. We assume that this is caused by different forms of human activity, which is related to their social characteristics, as well as to the characteristics of the space in which they operate. In other words, if people’s activities are different, the social spaces, created because of this are different, too. Functioning and meeting basic human needs are basic factors of spatial diversity. Social geography therefore deals with the population and space at the same time. The starting point could be space, the diversity of which we try to explain with different ways of human activity. In other cases, the origin can be found in different social characteristics of people, where spatial conditions are the result of different forms of their action and activities. The actors who create space are people - individuals and social groups.